Environmental Sustainability And Economic Growth: Policy Implications For Developing Countries - Bekti Utomo; Dodi Setiawan Riatmaja; Johny Aninam; Fajar Satriyawan Wahyudi (Nomico, 2024)
Environmental sustainability and economic growth are often considered to be two conflicting goals, especially in developing countries that face significant challenges in managing natural resources while pursuing economic growth. This research explores the complex relationship between environmental sustainability and economic growth in developing countries, with the aim of identifying policies that support sustainable economic growth. The methods used include literature reviews and thematic analysis to identify key patterns and relationships in existing studies. The research results show that although economic growth is often accompanied by increases in resource consumption and pollutant emissions, developing countries can achieve sustainable growth through strengthening environmental regulations, investing in green technologies, and increasing public awareness. Economic diversification, such as the development of sustainable tourism and organic agribusiness, can also reduce pressure on natural resources and create new economic opportunities. The proposed policy implications include increased environmental regulations, support for green technologies, and public education efforts to support environmentally friendly practices, with an integrated approach that ensures a balance between economic growth and environmental protection.